The relationship betweenparityand the incident of perinealruptures on women’s physiological maternity - Evi Rosita; Siti Nurnaningrum (Universitas 'Aisyiyah Yogyakarta, 2019)
There are about 2.8 million incident of perineal rupture in maternal physiological labor. In 2050,it is estimated that the incidence of perineal rupture can be 6.3 million if it is not accompanied by a good midwifery care. In 2016, in Trawas, there was (89%) perineal rupture in primiparas and (57%) perineal rupture in multiparas. Perineal rupture incidences due to parity were still very high. This study aims to analyze the relationship between parity and the incidence of perineal rupture . It is quantitative studyusing a cross sectional approach, by using analysis of physiological maternity women medical record data from January to April 2017 of 130 peoplein Trawas Public Health Center, Mojokerto Regency.The dataanalysis used was Chi - Square , indicated by p value = 0,000 with ɑ = 0,05. It means that the value of p ɑ, so H1 is accepted. It can be concluded that there is a relationship between parity and the incidence of perineal rupture on physiological maternity women in Trawas Public Health Center,Mojokerto Regency. Midwives can apply collaboration with patients and their families to have physical and psychologicalpreparation with an alternative of hypnobirthing methods.